Cold tolerance of some Iranian wild grape (V. vinifera ssp sylvestris) genotypes - Baneh, Hamed Doulati; Aslanpour, Mohammad (The Indian Journal of Agricultural Sciences, 2020)
All grape cultivars belong to Vinifera species are cold sensitive and (depend on cultivar) can be damaged by the temperature around -15 to -20°C. In this research, the cold tolerance of some Iranian wild grape (Vitis vinifera ssp sylvestris) genotypes was evaluated. After the leaf fall the 4 bud cuttings were prepared from the growing vines in Kahriz Horticultural Research Center in Urmia and then treated with freezing temperatures (-15, -18, -21, -23 and 4°C as a control) in a cold chamber. The percentage of burst buds in greenhouse condition and the percentage of died primary and secondary buds of each genotype in chilling temperature were measured. Electrical conductivity (EC) of buds and cane tissue was also measured. With decreasing temperature, the rate of primary and secondary bud injury increased and there was a significant difference in cold tolerance among tested genotypes. Approximately all Iranian wild grape genotypes were sensitive to cold stress above -15°C but among them, there were moderate cold tolerant genotypes too. H6 and H4 interspecies hybrids with Labrusca species showed higher cold tolerance compared to wild grape genotypes. These results will be valuable for selection of cold tolerance germplasm to use for cold tolerance breeding.